Slopes geometric model: An automatic Pre-DInSAR analysis. (June 2017) - Fernandez, Paz; Moya-Delgado, Sergio
Abstract: Geometric constraints impose one of the limiting factors in successfully applying the DInSAR technique in hilly areas. These limitations are related to the combination of SAR-image characteristics, due to the incidence angle of the sensor during the acquisition, and the properties of the orientation and slope angle. Consequently, a Pre-DInSAR geometric analysis is highly recommended to detect the areas where the DInSAR technique will be feasible. This previous phase implies some GIS software processes. To simplify this process and avoid human errors, we have developed an automatic model created with Model Builder™ ArcGIS software. This paper presents the model as well as an example of its application to an area previously analysed manually in order to validate the model. This pre-DInSAR analysis could increase the success of DInSAR studies and eliminate possible wrong justifications in the areas in which DInSAR results are unfeasible. Highlights: Slope geometry limits the success of DInSAR technique application in hilly areas. A geometric analysis prior to applying the DInSAR technique helps to detect areas where it will be feasible. We present a model developed to automatize and simplify the geometric considerations and avoid human errors. The model developed is effective, quick and easy: a DEM and a few minutes are needed to select DInSAR application areas.